BIOECOLOGICAL PROPERTIES OF MEDICINAL SPECIES OF THE MINT FAMILY (LAMIACEAE) - Z. A.Yusupova; Sayramov Fayzullo Baratjon o’g’li; Yormatova Oygul Abduqahhor qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The mint family (Lamiaceae) is one of the biggestplant families on earth. Its representatives are widespread in warm and temperate climatecountries.The mint family is one of the widespread families in the flora of Uzbekistan and is distinguished from other families by its wealth of useful species. Representatives of such groups as Marrubium alternidens Rech., Melissa officinalis L., Menthaarvensis L., Origanum tytthanthum Jontseh, Lagochilus hirsutissimus Vved.have been used in medicine, food, confectionery and perfume industry since ancient times.69 species belonging to 26 genera of the Lamiaceae family have medicinal properties, among the genera Lagochilus Bunge ex Benth. with 11 species, Ziziphora L. with 8 species, Salvia L. with 7 species, Dracocephalum L. with 7 species are the leaders. It was found that PerovskiaKar., Stachys L. with 4 species, Mentha L., Nepeta L. with 3 species, Lycopus L., Lamium L., Scutellaria L. with 2, and only 1 of the remaining 14 families have medicinal representatives.